Homogeneity Test on Collimators for Boron-Neutron Capture Therapy based on SNI 8506:2018 - S. Santosa; K. Khotimah; H. Yasmine (Atom Indonesia, 2023)
A serial homogeneity test based on Indonesian Standard SNI 8506:2018 were undertaken to investigate 12 manufactured collimators by using double wall single image radiography (DWSI) technique with an x-ray machine ranging from 120 to 150 kV. The standard stated that the film density should be measured on seven different points, and the result obtained must not exceed Â± 0.05 from the average density. This paper outlines a testing work for the collimators, calculating the density on six different points in the film. Six different points were selected due to technical constrains of the collimator manufacturing and radiography capabilities of the selected laboratory. The results of film the density for the 12 collimators are: (1) 2.59; (2) 2.57; (3) 2.14; (4) 1.88; (5) 2.10; (6) 1.96; (7) 2.33; (8) 2.28; (9) 2.06; (10) 2.18; (11) 2.24; and (12) 2.33. The result shows that collimator-2 has the most homogenous density. This study concludes that established parameters and process are needed to manufacture the collimator for BNCT in achieving proper performance testing based on the standard.